Acquisition- of articulatory skill in Kannada- speaking children of 3-7 years - NP, Nataraja; Bhardwaj, Anil K; MS, Malini (Journal of All India Institute of Speech and Hearing)
Articulatory patterns of speech develop as one aspect of physiological system, encompassing total growth and development of an individual in union with maturation and learning. Articulation depends upon a continuous process of development from a simple and homogenous medium to complex, modified differential level of growth. Articulatory acquisition or the learning of a system of sounds require the ability to produce different phonetic features such as voicing, aasality, etc., of the phonemes. These phonetic features are present in babbling stage itself. When one says that a child has learnt a sound, it not only means that the child has learnt the distinctive features necessary, but also that it is accepted by the child’s linguistic community